(untitled) (Boletin Médico de Postgrado, 2020)
Oral anticoagulant treatment with vitamin K inhibitor drugs such as warfarin has been used for decades for the therapy and prevention of thromboembolic disease with widely known side effects but with well-proven clinical utility. To determine the proportion of mortality and hospitalization of the anticoagulation and thrombosis clinic of the ASCARDIO Regional Cardiovascular Center in 2017 a descriptive cross-sectional study was carried out that included a sample of 294 patients. The results show that the main indication for anticoagulation was atrial fibrillation (73%) followed by venous thromboembolic disease (13%) and myocardial ischemia (9%). An 11.7% mortality rate was observed. The mean age of the deceased was 65 years with a slight prevalence of the female sex (53%). The main cause of death was cardiac (58%) and 65% of the deceased patients were taking warfarin at the moment of death. A 10% hospitalization rate was observed with an average age of hospitalized patients of 66 years; 52% were females. The main cause of hospitalization was cardiac (60%) followed by hemorrhage (18%) and 90% of the patients were taking warfarin at the time of hospitalization. The risk analysis for mortality and hospitalization according to cause and status of warfarin did not show statistical significance. There was a higher proportion of deaths (45%) and hospitalization (17%) in the group admitted with a diagnosis of myocardial ischemia.